Conhecimento experto em tradução: aferição da durabilidade de tarefas tradutórias realizadas por sujeitos não-tradutores em condições empírico-experimentais - Igor Antonio Lourenco da Silva (2007)
This thesis reports on an ongoing project EXPERT@ Expert knowledge in translation: modeling peak performance (CNPq 479340/2006-4), developed at LETRA (Laboratory for Experimentation in Translation), at Faculdade de Letras, UFMG. The thesis presents threedifferent and complementary approaches to data pertaining to two translation tasks carried out under experimental conditions with a keylogging software (Translog©) by four medicine expert researchers. The first approach draws on Shreves (2006) proposal of interface between translation studies and expertise and expert knowledge studies and examines the impact of the independent variable domain knowledge (SCARDAMALIA; BEREITER, 1991) on the tasks on the basis of the following dependent variables: pauses and recursiveness (ALVES, 2005;BUCHWEITZ; ALVES, 2006), segmentation (DRAGSTED, 2004, 2005), cognitive rhythm (JAKOBSEN, 2002), task representation (CHI, 2006b) and durability (ALVES; GONÇALVES, 2007). Results show that (i) there is significant impact of domain knowledge on recursiveness, the orientation phase and the level of segmentation; and (ii) durability of the translation task is related to task representation and the translation project implemented by the subjects, both related in turn to the type of segmentation. The second approach examines durability (ALVES; GONÇALVES, 2007) drawing on Rhetorical Structure Theory (RST)(TABOADA; MANN, 2006a, 2006b). The analysis shows that building a target text along the lines of the rhetorical structure of the source text does not necessarily entail more durable and coherent target texts, the implication being that choosing rhetorical structures unlike those inthe source text, particularly at low levels, may have a positive impact on target text coherence and consequently on task durability. The results in both the first and second approaches single out one of the subjects as having a different profile and performing more durable tasks. The third approach in this thesis focuses on that particular subject and analyses his text production from the perspective of (de)metaphorization (STEINER, 2001a, 2002) as one of the sources of target texts properties. Results point to high metaphoricity in both source and target texts, (de)metaphorization being a relevant feature in the subjects translation process, for which he relies on his domain and discourse knowledge. Results also show a regular pattern of orientation pauses before each clause complex and ongoing revision, so that the subject attains a highly durable output by the end of the drafting phase.